1997
DOI: 10.1093/sleep/20.10.858
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on Human Sleep and Circadian Rhythms of 17 Days of Continuous Bedrest in the Absence of Daylight

Abstract: As part of a larger bedrest study involving various life science experiments, a study was conducted on the effects of 17 days of continuous bedrest and elimination of daylight on circadian rectal temperature rhythms, mood, alertness, and sleep (objective and diary) in eight healthy middle-aged men. Sleep was timed from 2300 to 0700 hours throughout. Three 72-hour measurement blocks were compared: ambulatory prebedrest, early bedrest (days 5-7), and late bedrest (days 15-17). Temperature rhythms showed reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Apart from the direct physical consequences of a severe locomotor disability there may be other sleep disrupting mechanisms as well. Monk et al . (1997) have shown that 17 days of continuous bed rest in the absence of day‐light flattens the amplitude of the core body temperature rhythm and leads to poorer subjectively rated sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the direct physical consequences of a severe locomotor disability there may be other sleep disrupting mechanisms as well. Monk et al . (1997) have shown that 17 days of continuous bed rest in the absence of day‐light flattens the amplitude of the core body temperature rhythm and leads to poorer subjectively rated sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The main human body clock resides in the suprachiasmatic nucleus (SCN) of the hypothalamus and the most important entraining factor of the clock is known to be environmental light (Duffy and Wright 2005). It has been shown, however, that in addition to the lighting conditions, factors such as prolonged bed rest and physical exercise may lead to changes in the human circadian rhythms (Mistlberger and Skene 2005;Monk et al 1997). It is probable that many ageing AGU adults often stay most of their day either in bed or otherwise physically inactive.…”
Section: Springermentioning
confidence: 99%
“…Yet despite over 50 years of bed-rest studies in humans, there is very little objectively-measured sleep data (Pavy-Le Traon et al, 2007). Of the few experimental studies investigating any sleep measure, many have not included baseline night recordings (Komada et al, 2006) or are confounded by experimental designs which manipulate circadian rhythm or light exposure (Monk et al, 1997), directly affecting sleep data. Thus, the effect of sustained bed rest on objective sleep parameters in healthy humans is not well known.…”
Section: Introductionmentioning
confidence: 99%